Barium-promoted hydrothermal stability of monolithic Cu/BEA catalyst for NH3-SCR. Issue 42 (10th October 2018) - Lin, Qingjin; Liu, Jingying; Liu, Shuang; Xu, Shuhao; Lin, Chenlu; Feng, Xi; Wang, Yun; Xu, Haidi; Chen, Yaoqiang
Abstract : The addition of Ba on the improvement of hydrothermal stability over Cu/BEA: (i) stabilize the dispersion of Cu species and suppress the formation of CuO clusters; (ii) the higher redox property. These two factors decide the higher hydrothermal stability over CuBa/BEA-HT rather than Cu/BEA-HT. Abstract : As a promising candidate for NO x elimination from the emission of diesel engines, the enhancement effect of Ba on the hydrothermal stability of cordierite supported CuBa/BEA at 600 °C for 48 h was investigated by XRD, NH3 -TPD, H2 -TPR, XPS, EPR, TEM and in situ DRIFTS. Different properties and amounts of active species are significant factors contributing to the enhanced hydrothermal stability of CuBa/BEA-HT. CuBa/BEA-HT has more Cu 2+ /Cu + redox-couples and stronger interactions than Cu/BEA-HT, indicating an excellent redox property of the active species in CuBa/BEA-HT. The better redox property of CuBa/BEA-HT produces more nitrates that easily participate in the NH3 -SCR reaction, which enhances the low-temperature activity. Furthermore, as observed from EPR and H2 -TPR, the appearance of more isolated Cu 2+ species and fewer CuO species also contribute to the higher hydrothermal stability of CuBa/BEA-HT.